Optimal Incentive Schemes with Many Agents - Mookherjee, Dilip (Review of Economic Studies, 1984)
The Grossman-Hart principal-agent model of moral hazard is extended to the multiple agent case to explore the use of relative performance in optimal incentive contracting. Under the assumption that the principal chooses incentive schemes to implement agent actions as Nash equilibria, necessary and sufficient conditions are derived for the optimality of independent contracts, of rank-order tournaments, and for attainability of the first-best. In this context the relation of the principal's welfare to the correlation between the underlying randomness in outputs of different agents is also investigated. Finally, some problems with the Nash equilibrium implementation assumption are discussed.